Improving activities to prevent recidivism among women based on modern international experiences - Umarxo`jayev Asadbek Shuxratjon o`g`li, Samatov Samatjon Kodir o’g’li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
In this article, improvement of prevention inspectors' activities to prevent recidivism among women based on modern international experiences, modern international experiences, their study, implementation and transformation into national legislation based on national customs and traditions, the field is a new there are suggestions and recommendations for bringing to the stage and improving.